KAJIAN PERTUMBUHAN DAN PRODUKSI PADA 8 VARIETAS KEDELAI (GLYCINE MAX L.) MERRIL DI LAHAN SAWAH TADAH HUJAN (STUDY OF GROWTH AND PRODUCTIONS EIGHT SOYBEAN VARIETIES (GLYCINE MAX L.) MERRIL ON NON IRRIGATION FARM) - Suharno, Suharno (Jurnal Ilmu-Ilmu Pertanian, 2006)
One of the success in cultivation of soybean is determined by the seed. In Sawahan, Bleberan, Playen, Gunung Kidul, it had been observed at eight varieties of soybean. Those are five good national varietions Galunggung (V 1), varietions Wilis (V 2), varietions Mahameru (V 3), varietions Malabar (V 4) and varietions Bromo (V 5) and three good local varieties varietions Local Imogiri (V 6), varietions Local Prambanan (V 7), and varietions Local Playen (V 8).The observation was done in November 2003 untail February 2004, its purpose is to know which varieties indicating the good soybean growth and product. The experiment used Randomized Complete Block Design with one factor and 3 replacations. The data is group into two kinds. Those are the growth consisting the number of branch, leaves, and the height and the product the consist of the number of pod, seed, and the weight of 100 soybean seeds. The results showed that application it concludes that good person grows bean it is variation Imogiri (V6), and the good bean of the production is varietion Imogiri (V6). Examinations use to factor of one it concludes that good person grows bean it is varietion and the good bean of the production is varietion local Imogiri.